CRISPR/Cas StNRL1 gene knockout increases resistance to late blight and susceptibility to early blight in potato - Norouzi, Moshen; Nazarain-Firouzabadi, Farhad; Ismaili, Ahmad; Ahmadvand, Rahim; Poormazaheri, Helen (Frontiers in Plant Science, 2024)
With the development of genome editing technologies, editing susceptible genes is a promising method to modify plants for resistance to stress. NPH3/RPT2-LIKE1 protein (NRL1) interacts with effector Pi02860 of Phytophthora infestans and creates a protein complex, promoting the proteasome-mediated degradation of guanine nucleotide exchange factor SWAP70. SWAP70, as a positive regulator, enhances cell death triggered by the perception of the P. infestans PAMP INF1.Using a CRISPR/Cas9 system, a construct was made to introduce four guide RNAs in the potato cultivar, Agria. Sixty putative transgenic lines were regenerated, in which ten transgenic lines with deletions were selected and analyzed. A mutant line with a four-allelic knockdown of StNRL1 gene was obtained, showing ~90% reduction in StNRL1 expression level, resulting in enhanced resistance to P. infestans. Surprisingly, mutant lines were susceptible to Alternaria alternata, suggesting that StNRL1 may play a role as a resistance gene, hence, silencing StNRL1 enhances resistance to P. infestans.